Motivasi Generasi Muda Dalam Memilih Pekerjaan - Ningsih, Uci; Siregar, Nurul Hidayah (Master Program in Sociology, Faculty of Social and Political Sciences, Universitas Sriwijay, 2025)
The motivation of the younger generation in choosing a job is experiencing a significant shift due to technological advancements, changing social values, and lifestyle transformation. Today, young people not only consider economic factors such as salary and job security but also prioritize work that aligns with personal interests, offers opportunities for learning and self-development, and provides meaningful contributions to society. This study aims to analyze the job motivation of young adults using a mixed-methods approach involving 80 respondents aged 18–35 years who are active students. Quantitative findings show that 70.4% of respondents emphasize the importance of social benefits from work, while 60.5% prioritize self-development as a crucial consideration in career decisions. Qualitative results further reveal that passion, mental-health-friendly work environments, and flexible time management are key aspects shaping their job choices. These trends illustrate that the younger generation tends to value intrinsic motivations and meaningful work over merely financial or formal job stability. The analysis refers to Max Weber’s theory of social action, which highlights that actions are driven by subjective meanings and personal interpretations of social situations. Weber categorizes social action into four types: instrumental rational action, value-oriented rational action, affective action, and traditional action. In relation to this study, job selection represents a conscious decision shaped not only by rational goals but also by values and emotional considerations held by individuals. Thus, young people's career preferences are not automatic responses to external stimulus, but thoughtful actions based on meaning, aspirations, and the desire for a fulfilling professional life.